Історія дослідження проблеми походження Трипілля-Кукутені в світлі нових даних - Бурдо, Н.Б. (Археологія, 2003)
У статті проаналізовано погляди дослідників на проблему генези трипільської культури за 100 років її вивчення з урахуванням нових даних щодо датування Тріпілля-Кукутені за СІ 4. В статье проанализирована проблема происхождения трипольской культуры в отечественной и зарубежной историографии. Прослеживается процесс эволюции взглядов исследователей по мере накопления источников и их зависимость от общих концепций, господствовавших в археологии в различные периоды, выделенные в изучении Триполья Е.К. Черныш. Анализ всех имеющихся в настоящее время данных позволяет подтвердить выводы о формировании начальных фаз культуры Триполье-Кукутени в Трансильвании и Прикарпатской Молдове на многокомпонентной основе. Однако можно утверждать, что роль культуры боян в этом процессе необоснованно преувеличена, а роль культур Карпатского бассейна недостаточно учитывается. Новые радиоуглеродные даты дают возможность с уверенностью утверждать, что буго-днестровская культура не могла быть субстратом трипольской. The article analyzes the problem of origin of the Trypils’ka culture according to home and foreign history of Ttypi Ilia-Kuku tern research. The author shows a process of development of researchers’ viewpoints as sources were accumulated and dependence of viewpoints upon general conceptions prevailing in archaeology at various times which are distinguished by E.K- Chemysh according to the Trypillia studies. An analysis of the whole present data permits to corroborate the conclusion on forming of Trypillia-Kukuteni in the phases at the beginning of culture in Transylvania and eastern Carpathian Moldova on the multi-component basis. However it can be confirmed that a part ofBoyan culture is exaggerated unfoundedly at this process, and apart of cultures of Carpathian basin is underestimated. New radiocarbon dates permit to confirmed with confidence Bugo-Dnistrovs’ka culture couldn’t be a substratum for Trypils’ka one.